The bricolage mode of emergency medical teams in China: deficient and in urgent need of transformation—A qualitative study - Wang, Li; Sheng, Ya-Wei; Qi, Xin-Ye; Li, Fang-shi; Qiu, Xin-Yu; Shao, Shen; Du, Yue (Frontiers in Public Health, 2024)
Emergency medical rescue plays a vital role in alleviating the harm of all kinds of emergencies to people's physical and mental health and life safety. The current emergency medical teams (EMTs) formation mode is not unified. We focused on the disadvantages of the bricolage mode of China EMTs and put forward empirical-based countermeasures to improve the emergency management ability of EMTs. From March to September 2022, 23 leaders of EMTs in North China (Tianjin) were selected by objective sampling method to conduct semi-structured in-depth interviews. Nvivo12.0 software was used for three-level coding. The disadvantages of the bricolage mode of EMT were analyzed. Based on the three-level coding, 150 initial concepts, 36 subcoding, 17 main coding, six categories, and two core categories were sorted out. Management structure, internal stability, and support are recognized as the crucial elements armed with the EMTs. The bricolage EMTs have disadvantages such as a chaotic management structure, weak internal stability, and inadequate support. It is necessary to construct full-time EMTs that incorporate a standardized personnel admission mechanism, full-time training and exercise mechanism, diversified incentive mechanism, and multi-agent cooperation mechanism, etc.